Meningkatkan Pembelajaran Keterampilan Menanam Kangkung Melalui Media Hidroponik bagi Siswa Tunagrahita Kategori Sedang di Kelas VII SLB Negeri Muara Bulian - Nining, Nining; Iswari, Mega (Jurnal Penelitian Pendidikan Khusus, 2022)
This classroom action research, the authors are interested in focusing on the title "Improving Kangkung Planting Skills Through Hydroponic Media for Students with Medium Category Mental retardation in Class VII SLB Negeri Muara Bulian". The action was carried out in 2 cycles where each cycle had 3 meetings. The total of all meetings in this study were 6 meetings divided into several stages of planning, action, observation and reflection. The implementation of the action in the first cycle of moderately mentally retarded students got the results of Subject A's initial ability performance test with a score of 36.3 in the first cycle getting a value of 54.5, and in the second cycle getting a score of 72.7. Subject F has initial ability with a value of 54.5, in the first cycle the score is 72.7, and in the second cycle the score is 90.9. Subject R with initial ability with a value of 45.4, in the first cycle a score of 63.6, and in the second cycle a score of 81.8. Based on the results obtained, it was concluded that hydroponic media in improving the learning of kale planting skills for students with moderate mental retardation in grade VII at SLB Negeri Muara Bulian